1995
DOI: 10.2134/agronj1995.00021962008700030017x
|View full text |Cite
|
Sign up to set email alerts
|

Sod Regrowth of St. Augustinegrass after Preemergence Herbicide Application

Abstract: St. Augustinegrass [Stenotaphrum secundatum (Walt.) Kuntze] sod production involves stolon regeneration from strips left from the previous harvest. Field studies were conducted to evaluate stolon regrowth and rooting following preemergence application of herbicides. Herbicides evaluated were atrazine [6‐chloro‐N‐ethyl‐N'‐(1‐methylethyl)‐1,3,5‐triazine‐2,4‐diamine], dithiopyr [S,S‐dimethyl 2‐(difluoromethyl)‐4‐(2‐methylpropyl)‐6‐(trifluoromethyl)‐3,5‐pyrldinecarbothioate], isoxaben [N‐[3‐(1‐ethyl‐l‐methylpropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 5 publications
7
19
2
2
Order By: Relevance
“…This practice may also lengthen the period of effective control of tropical signalgrass. Dinitroaniline herbicides can reduce rooting and cause injury to immature turfgrass (Bingham 1974), resulting in poor root development and problems with sod slab integrity when lifting the turfgrass sod during harvest (McCarty et al 1995). McCarty et al (1995), however, reported that no long-term adverse effects occurred from a single application of dinitroaniline herbicides to St. Augustinegrass sod.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This practice may also lengthen the period of effective control of tropical signalgrass. Dinitroaniline herbicides can reduce rooting and cause injury to immature turfgrass (Bingham 1974), resulting in poor root development and problems with sod slab integrity when lifting the turfgrass sod during harvest (McCarty et al 1995). McCarty et al (1995), however, reported that no long-term adverse effects occurred from a single application of dinitroaniline herbicides to St. Augustinegrass sod.…”
Section: Resultsmentioning
confidence: 99%
“…St. Augustinegrass sod production involves producing a dense, uniform, healthy stand of turfgrass; harvesting the sod; and then promoting vegetative regrowth from strips or ribbons (7 to 10 cm) of remaining turfgrass plant material to generate a subsequent crop (McCarty et al 1995). This cycle requires 8 to 14 mo to complete, leaving significant areas of bare soil open Volume 18, Issue 2 (April-June) 2004 to weed invasion for long periods (McCarty and Cisar 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Em outros países, vários pesquisadores destacaram a viabilidade do uso de herbicidas aplicados em pré e pós-emergência em vá-rios tipos de gramados, a exemplo de atrazina, oxadiazon, quinclorac, sethoxydim, entre outros, bem como a possibilidade da utilização desses produtos em mistura em tanque, de forma a maximizar os efeitos dos diferentes mecanismos de ação no controle das plantas daninhas (Turner et al, 1990;McCarty et al, 1995;Johnson & Carrow, 1999;Brecke et al, 2001;Fagerness et al, 2002). Contudo, Christoffoleti & Aranda (2001) ressaltaram que não existe regra única de recomendação de herbicidas, sendo, portanto, necessárias recomendações diferenciadas, dependendo do nível de toxicidade tolerado pelo gramado.…”
Section: Introductionunclassified
“…Em outros países, vários pesquisadores destacaram a viabilidade do uso de herbicidas pré e pós-emergentes em vários tipos de gramados, a exemplo de atrazina, oxadiazon, quinclorac, sethoxydim, entre outros, bem como a possibilidade do emprego desses produtos em mistura em tanque, de forma a maximizar os efeitos dos diferentes mecanismos de ação no controle das plantas daninhas (Turner et al, 1990;McCarty et al, 1995;Johnson & Carrow, 1999;Brecke et al, 2001;Fagerness et al, 2002 Em 12/1/2006, os gramados foram cortados à altura de 3 cm com auxílio de um aparador de grama motorizado e, após dois dias, foram realizadas as aplicações dos tratamentos. As aplicações foram realizadas no período da manhã, em condições de temperatura de 27 ºC, solo úmido e umidade relativa do ar em torno de 64%.…”
Section: Introductionunclassified